2011
DOI: 10.2484/rcr.v6i4.624
|View full text |Cite
|
Sign up to set email alerts
|

Coracoid fracture with recurrent AC joint separation after Tightrope repair of AC joint dislocation

Abstract: We present a case of failure of acromioclavicular joint (ACJ) reduction that was performed with low-profile, double-metallic button technique (Tightrope; Arthrex Inc). The patient presented with coracoid fracture and loss of reduction within eight weeks of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Fractures after AC reconstructions involving transcoracoid drilling have been reported in the literature. 6 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Fractures after AC reconstructions involving transcoracoid drilling have been reported in the literature. 6 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Second, in order to prevent clavicle fractures at the suture hole, it is essential to avoid excessive drilling of the suture hole during ACJ reconstruction and pay attention to the widening of suture holes at radiography images. Over-tensioning of the sutures [14, 16], osteolysis from a soft tissue reaction [15], technical factors due to the operator such as multiple entry-point drilling or suture holes that are not located in the center of the bone [1, 9], and poor adherence of the patients [7] are considered to be the mechanisms that can cause fractures near the suture hole. In the present case, multiple drilling holes were observed near the suture-button entry-point during the present surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] More recently, as use of the arthroscopic transcoracoid technique has increased, several reports of associated coracoid fracture have emerged. [13][14][15] Both Gerhardt et al 13 and Bindra et al 14 reported isolated fractures after the use of different types of coracoid buttons. More worrisome is a report by Milewski et al 15 that retrospectively reviewed a case series of different anatomic reconstruction techniques.…”
Section: Discussionmentioning
confidence: 99%